KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI DUSUN MONTONG TEKE, DESA JAGO, KECAMATAN PRAYA, KABUPATEN LOMBOK TENGAH - Sovi Natun Najah; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
Jago is a village in Praya District, Central Lombok Regency. The study was conducted using observational methods. Based on the study, it was found that yard plants in Hamlet Montong Teke, Jago Village, Praya District, Central Lombok Regency had an H’=1,89 indicating moderate diversity, moderate distribution, and moderate community stability.